Взаємодія оксиду нікелю (II) з фосфато-фторидною системою літію - Нагорний, П. Г.; Корнієнко, З.І.; Бойко, Р.С.; Городилова, Н.О.; Баумер, В.М.; Слободяник, М.С. (Видавничий дім "Академперіодика" НАН України, 2007)
The interaction of nickel dioxide with solutions-melts of the system LiPO3−LiF has been stu- died. Phase formation of LiNi2P3O10, Li2Ni3(P2O7)2, LiNiPO4, and Li2NiPO4F is establi- shed. Synthesized complex phosphates are investigated by X-ray phase analysis, IR-spectroscopy, and quantitative chemical analysis. The structure of Li2Ni3(P2O7)2 has been determined from single-crystal X-ray diffraction data. It crystallizes in the monocline syngony with unit-cell parameters a = 7.1992(45)˚ A, b = 7.7541(10)˚ A, c = 9.3415(48)˚ A, β = 110.34(5) ◦ , V = 488.96(976)˚ A3 , and space group P21/с.